EFEKTIVITAS TOLERANSI BERAGAMA DALAM MEWUJUDKAN PERDAMAIAN MELALUI PENCAPAIAN PROGRAM SDGs - Wulandari Rahmawati; Nur Sukmawati; Jayanti Armida Sari (Pusat Kajian Berkelanjutan UIN Sulthan Thaha Saifuddin Jambi, 2023)
Improving the quality of religious life will emerge if the goals of the SDGs program are implemented properly. Therefore, the important role of religious people is needed to accelerate efforts to increase religious tolerance in realizing national peace. In Indonesia, the role of a religious leader is needed in overcoming conflicts or debates related to religion by using a religious language approach. In this case religion and religious leaders can be used as an instrument as a national development tool to create religious tolerance which is the main issue of the SDGs. The method used in this article is the literature review method. The data used is in the form of secondary data in the form of the results of thoughts contained in both national and accredited books and journals which contain the topic of religious tolerance with the SDGs program. The results of this study explore the issues of national development in realizing peace